Rhodian Amphoras from Butrint (Albania): Dating, Contexts and Trade - Aleotti, Nadia (Journal of Hellenistic Pottery and Material Culture, 2017)
The paper focuses on Rhodian amphoras from the Butrint Roman Forum Excavations Project 2011–2014, carried out under the direction of the Notre Dame University (Indiana, USA) in collaboration with the Albanian Institute of Archaeology in the ancient city of Butrint (southern Albania). Considering their great informative potential, Rhodian amphoras are studied in terms of both dating and trade, focusing on the contexts they come from, on precise dates given by stamps and on the contribution of Rhodian amphoras to investigate and assess the commercial trade of Hellenistic Butrint.